Luminescence quantum efficiency at 1.5 μm of Er3+-doped tellurite glass determined by thermal lens spectroscopy - Figueiredo, M. S. [UNESP]; Santos, F. A. [UNESP]; Yukimitu, K. [UNESP]; Moraes, J. C S [UNESP]; Silva, J. R.; Baesso, M. L.; Nunes, L. A O; Andrade, L. H C; Lima, S. M. (Elsevier, 2013)
Erbium doped tellurite glasses (TeO2 + Li2O + TiO2) were prepared by conventional melt-quenching method to study the influence of the Er3+ concentration on the luminescence quantum efficiency (η) at 1.5 μm. Absorption and luminescence data were used to characterize the samples, and the η parameter was measured using the well-known thermal lens spectroscopy. For low Er3+ concentration, the measured values are around 76%, and the concentration behavior of η shows Er-Er and Er-OH- interactions, which agreed with the measured lifetime values. © 2013 Elsevier B.V. All rights reserved.
Keywords: Tellurite glass Erbium Luminescence quantum efficiency Thermal lens spectroscopy